Clinical review: immunomodulatory effects of dopamine in general inflammation - Beck, Grietje; Brinkkötter, Paul-Thomas; Dacho, Christine; Schulte, Jutta; Ackern, Klaus van; Woude, Fokko J. van der; Yard, Benito A. (Critical care, 2004)
Large quantitaties of inflammatory mediators are released during the course of endotoxaemia. These mediators in turn can stimulate the sympathetic nervous system (SNS) to release catecholamines, which ultimately regulate inflammation-associated impairment in tissue perfusion, myocardial impairment and vasodilatation. Treatment of sepsis is based on surgical and/or antibiotic therapy, appropriate fluid management and application of vasoactive catecholamines. With respect to the latter, discussions on the vasopressor of choice are still ongoing. Over the past decade dopamine has been considered the 'first line' vasopressor and is frequently used to improve organ perfusion and blood pressure. However, there is a growing body of evidence that dopamine has deleterious side effects; therefore, its clinical relevance seems to be more and more questionable. Nevertheless, it has not been convincingly demonstrated that other catecholamines are superior to dopamine in this respect. Apart from its haemodynamic action, dopamine can modulate immune responses by influencing the cytokine network. This leads to inhibition of expression of adhesion molecules, inhibition of cytokine and chemokine production, inhibition of neutrophil chemotaxis and disturbed T-cell proliferation. In the present review we summarize our knowledge of the immunomodulatory effects of dopamine, with an emphasis on the mechanisms by which these effects are mediated.